2021
DOI: 10.1038/s41598-021-03857-w
|View full text |Cite
|
Sign up to set email alerts
|

Ni–citric acid coordination polymer as a practical catalyst for multicomponent reactions

Abstract: Coordinative polymers (CP) are a subclass of Metal–organic frameworks (MOFs) with porous microstructures which have been widely synthesized in recent years and applied in various fields especially in catalysis science. In this work Coordinative polymers (CP) of nickel and citric acid (CA) was prepared as a new catalyst (Ni-CP) and applied in organic multicomponent reactions. The obtained catalyst was characterized by SEM, WDX, EDS, AAS, FT-IR, XRD and BET analysis. N2 adsorption–desorption isotherms indicate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…According to previous literature, [ 55 ] a plausible mechanism for performing this reaction in the presence of Lewis acid can be suggested in Figure 5. This mechanism has several stages, the first of which involves the activation of the aldehyde by the Ni@KP222/Fe 3 O 4 @PEG catalyst.…”
Section: Resultsmentioning
confidence: 89%
“…According to previous literature, [ 55 ] a plausible mechanism for performing this reaction in the presence of Lewis acid can be suggested in Figure 5. This mechanism has several stages, the first of which involves the activation of the aldehyde by the Ni@KP222/Fe 3 O 4 @PEG catalyst.…”
Section: Resultsmentioning
confidence: 89%
“…These absorption peaks were not observed in the spectra of the prepared Zn‐CA‐MOFs, whereas the Zn‐CA‐MOF spectrum showed two absorption peaks related to the vibration of the C=O bonds of aliphatic carboxylic acid groups at 1560 cm −1 . [ 44 ] The carbonyl absorption peak shifts, from 1703 cm −1 in the pure citric acid to the lower wavenumber (1560 cm −1 ) in the final Zn‐CA‐MOFs, represent the interaction between Zn and citric acid (Figure 1c). In addition, the peaks at the region of 2922–2999 cm −1 are the most important peaks that can be regarded as the characteristic of the aliphatic C─H stretching vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results effectively coincide with XRD patterns simulated from powder X-ray data of porous Zn-based MOFs with a cubic crystal phase, showing that the structure agrees with the literature reports. [45][46][47] The EDX spectrum results indicate the presence of Zn (9.53 W %), O (45.17 W %), carbon (32.48 W %), and nitrogen (12.52 W %) species in the obtained porous Zn-CA-MOFs' catalyst (Figure 3). These observations support the high purity of the prepared catalyst.…”
Section: Structural Analysismentioning
confidence: 99%
“…The results of using different conditions in model reaction presented in entries (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Although the reaction time with 15 or 20 mg of the catalyst is slightly less than the reaction time with 10 mg of catalyst, no noticeable change in e ciency was seen. For this reason, the optimal amount of catalyst was chosen to be 10 mg. By using the introduced catalyst components separately in the model reaction, it can be concluded that the prepared nano-catalyst shows better results in proceeding the three-component synthesis of imidazole derivatives.…”
Section: The Morphological Features and Particle Size Of The New Magn...mentioning
confidence: 99%
“…The total synthetic approach adjusts to the basic principles of sustainable chemistry that purpose to reduce the production of hazardous materials under various reaction conditions [1][2][3] . The designed-procedures for the preparation of nanomaterials including magnetic nanoparticles and their catalytic activities are entirely veri ed in the eld of greener and atom-economic reactions especially multicomponent reactions [4][5][6][7] . On the other hand, the use of magnetic decorated organic species is gaining signi cant attention in the eld of catalysis for organic transformations, mainly due to opportunities in providing new structural changes [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%